Relevance of multimedia in education. - J. Badi, Maimona; Zeki, Akram M.; Mahmud, Murni (IIUM Press, 2011)
The changes in the education field are experiencing improvements in using media services. The old days of an educational institution having an isolated audio-visual department are becoming less existing now days. The growth in use of multimedia within the education sector has accelerated in recent years, and looks set for continued expansion in the future.